Prospective Analysis of The Coffee Agrotourism Business - Putu Yudy Wijaya; I Made Endra Kartika Yudha; Ni Nyoman Reni Suasih (SOCA: Jurnal Sosial Ekonomi Pertanian, 2022)
Sustainable tourism will be carried out well if the community participates. However, agro-tourism in Catur Village has not been able to develop and make a positive contribution to the community. The objectives of this study are to find out the problems faced in the framework and the role factors of agro-tourism development in Catur Village, Kintamani District, Bangli. This study used prospective analysis. The type of data used in this study is primary data obtained from informants, namely: agro-tourism businesses, farmers, government, community groups, tourism operators, through focus group discussions (FGD) and interviews. The key element matrix analysis was performed with MICMAC (Matrix of Cross Impact Analysis) analysis. The results showed that Catur Village have the potential for agro-tourism development, but there are still some problems, such as lack of community knowledge and skills related to agro-tourism, inadequate marketing techniques, lack of vision and strategy, and lack of optimal institutions. The factors that influence the development of agro-tourism are environment and culture, integration relations, facilities and infrastructure, institutions, and social society